Meningkatkan Minat Belajar menggunakan Model Pembelajaran Demonstrasi pada Materi Gerak Vertikal Ke Atas, Gerak Vertikal Ke Bawah, dan Gerak Jatuh Bebas - Marsya Indah Yunita; Nurul Maharani; Dimas Raskian Aji; Wahyu Kurniawati (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research is intended to provide an in-depth understanding of physics material regarding upward vertical motion, downward vertical motion, and free fall motion using a demonstration learning model. The purpose of this article is to provide a reference learning model that can be used by teachers when presenting physics material so that it is not boring and is easy to understand. This learning model is effectively applied in almost all physics material, including upper vertical motion, lower vertical motion, and also free fall motion. Because the teacher's role is important in increasing students' interest in learning and making the class atmosphere more enjoyable when delivering the material, this article is very helpful and can be a reference source that can be used when determining the model for learning movement material.